Personality characteristics and the decision to become and stay self-employed - Marco Caliendo; Frank Fossen; Alexander Kritikos (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper systematically investigates whether different kinds of personality characteristics influence entrepreneurial development. On the basis of a large, representative household panel survey, we examine the extent to which the Big Five traits and further personality characteristics, which are more specifically related to entrepreneurial tasks, influence entry into self-employment and survival of self-employed persons in Germany. The empirical analysis reveals that among the specific characteristics in particular risk attitudes and locus of control have strong effects on entry and survival. With respect to the Big Five approach, in particular the traits openness to experience and extraversion and to a lower extent agreeableness and neuroticism help to explain entrepreneurial development. The explanatory power of the Big Five is comparable to one of the most prominent determinants of entrepreneurship - education - and approximately three times larger than parental selfemployment.
Keywords: D81; J23; M13; 330; entrepreneurship; personality; Big Five; risk aversion; locus of control; Unternehmer; Selbstständige; Persönlichkeitspsychologie; Deutschland